Mortars, plasters and pigments—research questions and sampling criteria - Gliozzo, Elisabetta; Pizzo, Antonio; La Russa, Mauro Francesco (Archaeological and anthropological sciences, 2021)
Within the Topical Collection, this paper represents an introductory contribution aimed at describing and discussing the research questions and the sampling criteria in the field of mortars, plasters and pigments studies. The paper is divided into three parts. In the first part, some terminological issues are clarified and the building archaeology is introduced as an indispensable method for sampling and interpreting archaeometric results. In the second part, the most common research questions are presented and discussed. Some case studies are also reported to clarify what the expected results may be. The sampling problem is faced in the third part, where the criteria for a representative, functional and suitable selection are provided.